The Effect of Labeling Genetically Modified Food on Perceptions of Accountability - Tracy Irani; Janas Sinclair (Journal of Applied Communications, 2004)
Differing viewpoints about labeling of genetically modified (GM) foods have created communication challenges. This experiment, using a college student sample, examined the impact of exposureto various types of GM food labels on perceptions of the accountability of government and industry as well as attitude toward GM foods. Results indicated that labeling message and salience (strength) affected subjects’ perceptions of government and industry accountability, which in turn affected attitude toward purchase as well as global attitudes toward GM foods. Results indicated that subjects perceived a stronger prescription-event accountability linkage when (1) the label indicating the presence of GM ingredients had strong salience and (2) when the label indicating lack of GM ingredients had weak salience. The findings showed the manufacturer’s product claim label created stronger accountability perceptions that industry is concerned with regulating GM foods than the mandatory FDA certified label. A key implication of the study is that communicating to consumers about governmental and industry efforts related to GM foods may be an effective way to achieve greater consumer support of controversial food technologies.